2013
DOI: 10.11113/jt.v62.1876
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Regeneration and Antioxidant Propertiesof Lycium Barbarum L. (Goji)

Abstract: Ethnobotanical studies has documented the consumption of goji by Chinese tribes since ancient times. Goji or scientifically known as Lycium barbarum L. belongs to Solanaceae family and native to some areas of China. The present study was conducted to determine the best explant and corresponding hormonal compositions for Goji in vitro regeneration. In addition, the age and organ of in vitro seedlings with the optimum level of antioxidant activity were also identified. For in vitro regeneration, leaves and nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In addition, Goji leaves have been described as a sustainable source of antioxidant compounds [ 9 , 10 ]. The biological properties have been related to complementary, additive, or synergistic interactions between the high content of vitamins, minerals (mainly calcium, iron, and zinc), and a diversity of polyphenols, alkaloids, and polysaccharides [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Goji leaves have been described as a sustainable source of antioxidant compounds [ 9 , 10 ]. The biological properties have been related to complementary, additive, or synergistic interactions between the high content of vitamins, minerals (mainly calcium, iron, and zinc), and a diversity of polyphenols, alkaloids, and polysaccharides [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported the use of BAP in combination with α-napthaleneacetic acid (NAA) to induce direct or indirect organogenesis, and indirect somatic embryogenesis of goji starting from node or leaf explants. One example is the study of Osman et al [21], where the best result of plantlet regeneration through indirect organogenesis was obtained combining BAP and NAA (both at 0.5 mg L −1 ) starting from leaf explants. Leaf explants were also identified as the better way to induce indirect somatic embryogenesis on Murashige and Skoog (MS) medium [22], added of 1.0 mg L −1 2,4-dichlorophenoxyacetic acid and 0.1 mg L −1 BAP [23].…”
Section: Seed Germination Shoot Induction and Multiplicationmentioning
confidence: 99%
“…In this context, tissue culture is a valuable technique to produce secondary metabolites, and many studies showed the improvements that can be obtained in many species such as, in the same Lamiaceae family, sage [3] and oregano [34]. The advantage to produce antioxidants by goji in vitro culture was also underlined by Osman et al [21] and Dutu et al [35] on 2-month old plantlets, using the conventional micropropagation. In particular, the latter Authors tested the influence of different lengths wave (white; blue 473 nm; green 533 nm; yellow 580 nm; red 680 nm) on TPC and TFC content of goji leaves.…”
Section: Determination Of Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%
“…Goji shrubs are propagated vegetatively, especially by semi-wooden cuttings and with great success in vitro [ 9 ]. According to Dzhugalov et al [ 10 ], the optimum quality fruit can be obtained under hot summer conditions.…”
Section: Introductionmentioning
confidence: 99%